Discovery and optimization of heteroaryl piperazines as potent and selective PI3Kδ inhibitors. Issue 1 (1st January 2020) - Zhou, Hua; McGowan, Meredeth A.; Lipford, Kathryn; Christopher, Matthew; Fradera, Xavier; Witter, David; Lesburg, Charles A.; Li, Chaomin; Methot, Joey L.; Lampe, John; Achab, Abdelghani; Shaffer, Lynsey; et al.
Graphical abstract: Abstract: A high-throughput screening (HTS) campaign identified a class of heteroaryl piperazines with excellent baseline affinity and selectivity for phosphoinositide 3-kinase δ (PI3Kδ) over closely related isoforms. Rapid evaluation and optimization of structure-activity relationships (SAR) for this class, leveraging the modular nature of this scaffold, facilitated development of this hit class into a series of potent and selective inhibitors of PI3Kδ. This effort culminated in the identification of 29, which displayed excellent potency in enzyme and cell-based assays, as well as favorable pharmacokinetic and off-target profiles.